Multiwavelength Brillouin-Raman fiber laser assisted by Rayleigh scattering - Raheleh, Sonee Shargh (2013)
Multiwavelength fiber lasers based on hybrid Brillouin-Raman gain configuration supported by Rayleigh scattering effect have attracted significant research interest due to the large numbers of channel generation from a single light source. When narrow bandwidth Brillouin gain combines with broad bandwidth Raman gain, hundreds of channels would be generated. In multiwavelength Brillouin–Raman fiber laser (MBRFL) architectures, dispersion compensated fiber is utilized as the nonlinear gain media. When a single laser launches into a distributed Raman gain area, it grows very fast through stimulated Raman scattering, and when it acquires threshold condition, it isback-scattered through nonlinear Brillouin and Rayleigh effects, inelastically and elastically inside the gain media respectively. After scattered lights experience amplification through stimulated Raman and Brillouin amplification, they saturate and consequently back-scatter once more. This phenomenon is dubbed as self-feedback seeding-effect which is the main principle of MBRFL generation. Normally, the other nonlinear effects such as four waves mixing is assisted by distributed Raman amplifier which generates self-lasing cavity modes that lead to the formation of turbulent waves. The interaction between laser cavity lines and the turbulent waves causes spectral broadening of laser lines that has a direct impact on the quality of Brillouin Stokes lines in terms of Stokes-optical signal to noise ratio (S-OSNR). In this work, it is proven that utilizing large effective area fiber (LEAF) in MBRFL enhances the S-OSNR of Brillouin Stokes lines effectively. Consequently, LEAF is used in the aim of suppressing the noise. In all the experiments which have done in this work, Brillouin pump power is fixed on higher level (8 dBm) due to producing the higher stimulated Brillouin scattering. However Raman pump power and Raman pump direction are two critical features which are studied in this thesis, since they play significant role in the MBRFL characteristics performances. Generation of flat amplitude MBRFL comprises higher number of channels with acceptable S-OSNR utilizing a single frequency Raman pump is the main objective of this research. Investigation and improvement of the characteristics of MBRFL utilizing LEAF is another aim of this work. In this work the optical characteristic performances of generated MBRFL output spectrum at three different configuration; conventional-MBRFL (CON-MBRFL), double-pass MBRFL (DP-MBRFL) and new forward-backward scattering combination-MBRFL (FBSCMBRFL) are investigated at different Raman pump powers and directions. It is obtainedthat the forward pumping scheme of CON-MBRFL configuration capable to produce flat amplitude MBRFL with 20 GHz channels spacing. Maximum 322 channels with acceptable average S-OSNR about 16 dB has been created with this structure, when 1525 nm Brillouin pump wavelength is launched into the linear cavity. In addition, 258 channels with 26 dB SOSNR, excellent uniformity, identical Stokes peak power and linewidth are generated via utilizing backward-Raman pumping scheme of DP-MBRFL configuration. Moreover, it is found that the new configuration FBSC-MBRFL is capable to enhance the Stokes lines count to 700 channels while a single forward-Raman pumping scheme is applied with 1 W power.